A EFFECT OF THE STUDENTS’ LEARNING INDEPENDENCE, SOCIAL INTELLIGENCE, AND ENGLISH READING SKILLS ON THEIR WRITING SKILLS OF ENGLISH RECOUNT TEXTS - Maskur; Burhanuddin Tola; Maruf Akbar (Program Pascasarjana Universitas Negeri Jakarta, 2020)
The aims of this research was to determine the effect of learning independence and social intelligence on English reading skills as well as on writing skills of English recount texts, both directly and indirectly. The method used in this study is a causal survey method, with a path analysis technique to test the effect of exogenous variables on endogenous variables. The population of this study was all students of Public Senior High School (SMAN), Grade XI in zone 2 in Depok District. A sample of 332 respondents was taken using cluster random sampling techniques for zone selection and simple random sampling for school and respondent selection. Data were collected using questionnaires for learning independence, social intelligence, and tests for reading skills and writing skills in English. The results showed that to some extent there was a positive effect both directly and indirectly of the students’ learning independence, social intelligence, and English reading skills on their writing skills for English recount texts.